2003
DOI: 10.1021/jf020549c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Microalgal Diets. 2. Influence on Odorant Composition and Organoleptic Qualities of Raw Oysters (Crassostrea gigas)

Abstract: Oyster farming is of real economic interest in France. Oyster farmers attach more and more importance to improving the growth and the quality of their oysters. Some fatty acids known to be aroma precursors originate from microalgae such as Skeletonema costatum and Tahitian isochrysis clone. These microalgae were used to fatten oysters in order to observe their role in the development of oysters' aroma. This study shows that the profile of fatty acids of oysters is influenced by the contribution of fatty acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
13

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 20 publications
0
29
0
13
Order By: Relevance
“…D'autres critères de sélection, tout aussi déterminants, ont été évoqués dans la littérature : il s'agit de la motivation Bernet et al, 2002) et la disponibilité des sujets (Linssen et al, 1993 ;. Plusieurs auteurs ont procédé à un entraînement des sujets orienté vers la description et la reconnaissance d'odeurs à partir de solutions de standards (Linssen et al, 1993 ;Piveteau, 2000 ;Rouseff et al, 2001 ;Fu et al, 2002 ;Lablanquie et al, 2002 ;Pennarun, 2003 (Linssen et al, 1993 ;Callement et al, 2001 ;Rouseff et al, 2001) ont réalisé systématiquement des séances de familiarisation des sujets avec le dispositif olfactométrique avant de passer aux véritables séances d'analyse. La méthode utilisée est inspirée de celle proposée par Moio et al (1995).…”
Section: C) Le Cas Des Extraits Dits « Non Manipulables »unclassified
See 2 more Smart Citations
“…D'autres critères de sélection, tout aussi déterminants, ont été évoqués dans la littérature : il s'agit de la motivation Bernet et al, 2002) et la disponibilité des sujets (Linssen et al, 1993 ;. Plusieurs auteurs ont procédé à un entraînement des sujets orienté vers la description et la reconnaissance d'odeurs à partir de solutions de standards (Linssen et al, 1993 ;Piveteau, 2000 ;Rouseff et al, 2001 ;Fu et al, 2002 ;Lablanquie et al, 2002 ;Pennarun, 2003 (Linssen et al, 1993 ;Callement et al, 2001 ;Rouseff et al, 2001) ont réalisé systématiquement des séances de familiarisation des sujets avec le dispositif olfactométrique avant de passer aux véritables séances d'analyse. La méthode utilisée est inspirée de celle proposée par Moio et al (1995).…”
Section: C) Le Cas Des Extraits Dits « Non Manipulables »unclassified
“…Un compromis doit être trouvé. En moyenne, le temps d'une analyse olfactométrique se situe entre 30 et 45 minutes (Miranda-Lopez et al, 1992a ;Linssen et al, 1993 ;Rouseff et al, 2001 ;Conner et al, 2001 ;Le Fur et al, 2003 ;Pennarun et al, 2003). Benn et Peppard, 1996 ont réalisé des analyses en GC-O d'une durée de 65 minutes sans interruption.…”
Section: G) La Répétabilité Dans La Descriptionunclassified
See 1 more Smart Citation
“…This indicated that C4_PC2 identified 'Hort16A'-like odour volatiles'. Turin (1996) found that ethylbenzaldehyde had a typical bitter almond Rychlik et al 1998, b Fazzalari 1978Euphytica (2011 odour and Pennarun et al (2003) found that 4-ethylbenzaldehyde was characterized by a minty and aniseed odour. Propanol is an alcohol with relatively weak odour and its concentration (Table 1) was below its odour threshold (Rychlik et al 1998 Labbe et al 2007;Miyazawa et al 2008).…”
Section: 'Flavour Impact' Volatiles Of a Chinensis Fruitmentioning
confidence: 99%
“…In oyster refinement, market‐sized Pacific cupped oysters ( Crassostrea gigas , Thunberg) are kept in basins and fed with algae to increase the oyster tissue weight and to change the sensorial properties of the oysters . Differences in odor, taste, and appearance between refined and non‐refined oysters have been shown when trained panelists were used for the evaluation . Refined Pacific cupped oysters have been characterized by a stronger grass odor, a sweeter, less salty and less bitter flavor, in comparison to non‐refined oysters .…”
Section: Introductionmentioning
confidence: 99%